Pengaruh Corporate Governance dan Stakeholder Engagement Terhadap Kualitas Sustainability Report - Monika, Dini Ernis; Taqwa, Salma (Universitas Negeri Padang, 2025)
This study aims to examine the effect of Board size of directors, independent commissioners, foreign ownership, and stakeholder engagement on the quality of sustainability report. The population used in this study consists of all non-financial sector companies listed on the Indonesia Stock Exchange in 2019-2023. The sample was determined using a purposive sampling, resulting in 31 companies as samples. The data used in this study are secondary data, specifically annual reports and sustainability reports obtained from the Indonesia Stock Exchange and the respective company websites. The analysis was conducted using multiple linear regression analysis using Eviews12 application. The results of the study indicate that independent commissioners and stakeholder engagement have a significant positive effect on the quality of sustainability reports. Meanwhile, board size and foreign ownership do not have an effect on the quality of sustainability reports in non-financial sector companies listed on the IDX in 2019- 2023. For future research, it is expected to chose other variabels that have effect on sustainability report quality.